PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE 11 (Studi Kasus Mahasiswa/i FEB Universitas Kristen Indonesia) - nabila, nabila; Wilson Rajaguguk (Fakultas Ekonomi Universitas Kristen Indonesia, 2024)
The current industrial environment is in a state of development and innovation must continue. Today's advanced technologies provide significant benefits by facilitating human tasks, enabling the completion of difficult and complex tasks in the short term. The purpose of this study was to find out information about product quality, price, and brand image on the decision to purchase an iPhone 11 smartphone within the scope of the Indonesian Christian University Management Study Program Student/I Faculty of Economics and Business. Obtaining information in this study from questionnaires and distributed to 50 respondents by making the respondents according to the character by means of purposive sampling. This study uses data processing by means of analysis of the coefficient of determination (R2), t test, F test, classical assumption test. Tests are carried out to find out information about each variable. The findings from the study state that price has a significant significant effect on purchasing decisions, the brand image variable also provides significant significance. All variables influence the decision to purchase the iPhone 11 smartphone by 78%, the rest of the unaccounted points come from variables not included in this study. The conclusion of this study is that the variables studied provide significance in the conditions of purchasing decisions made. Keywords: Product Quality, Price, Brand Image, Purchase Decision